Oxford photo dictionary - OUP (Oxford University Press, Oxford, 1997)
The Oxford Photo Dictionary by Oxford University Press (OUP) is a vocabulary-building resource that uses photos to illustrate and define words. It$1 (Bs especially popular in language learning, as it visually supports word association and comprehension. Adding abstract concepts to a photo dictionary can be challenging since abstract terms (like (3z(Bfreedom,(3y z(Bjustice,(3y (Bor (3z(Blove(3y(B) lack a physical form.s